The Role of Vascular-Immune Interactions in Modulating Chemotherapy Induced Neuropathic Pain - Valentine, Tameille; Hardowar, Lydia; Elphick-Ross, Jasmine; Hulse, Richard P.; Paul-Clark, Mark (Frontiers in Pharmacology, 2022)
Chemotherapy causes sensory disturbances in cancer patients that results in neuropathies and pain. As cancer survivorships has dramatically increased over the past 10 years, pain management of these patients is becoming clinically more important. Current analgesic strategies are mainly ineffective and long-term use is associated with severe side effects. The issue being that common analgesic strategies are based on ubiquitous pain mediator pathways, so when applied to clinically diverse neuropathic pain and neurological conditions, are unsuccessful. This is principally due to the lack of understanding of the driving forces that lead to chemotherapy induced neuropathies. It is well documented that chemotherapy causes sensory neurodegeneration through axonal atrophy and intraepidermal fibre degeneration causing alterations in pain perception. Despite the neuropathological alterations associated with chemotherapy-induced neuropathic pain being extensively researched, underlying causes remain elusive. Resent evidence from patient and rodent studies have indicated a prominent inflammatory cell component in the peripheral sensory nervous system in effected areas post chemotherapeutic treatment. This is accompanied by modulation of auxiliary cells of the dorsal root ganglia sensory neurons such as activation of satellite glia and capillary dysfunction. The presence of a neuroinflammatory component was supported by transcriptomic analysis of dorsal root ganglia taken from mice treated with common chemotherapy agents. With key inflammatory mediators identified, having potent immunoregulatory effects that directly influences nociception. We aim to evaluate the current understanding of these immune-neuronal interactions across different cancer therapy drug classes. In the belief this may lead to better pain management approaches for cancer survivors.